EXPLORATION OF THE ANXIETY BY NOVICE AND PROFESSIONAL DRIVERS - Sáiz Vicente, Enrique; Bañuls Egeda, Rosa; Monteagudo Soto, M. José (Anales de Psicología / Annals of Psychology)
This work puts of manifest the importance that has the study of the emotional processes and cognitivemotivacional in the activity of driving. For this are described the professional and novice drivers sample personnel in the work and is accomplished an analysis of the characteristics of the same, as well as a factorial analysis with the punctuations obtained in the items from the questionnaire I.S.A.T. (Bañuls, 1993) for both drivers samples.They are obtained some very interesting results that show how are grouped, in a way relatively independent the items of the self-evaluation in connection with four general factors, being these different for each one of the drivers samples, according to his different factorial weight.